2020
DOI: 10.1371/journal.pone.0234389
|View full text |Cite
|
Sign up to set email alerts
|

Chemoradiation for cervical cancer treatment portends high risk of pelvic floor dysfunction

Abstract: To assess the impact of chemoradiation on pelvic floor (PF) muscle function after the treatment of cervical cancer (CC). Methods We performed a prospective cohort study of women between the ages of 20 and 70 years old who had a diagnosis of CC. Patients were treated with chemoradiation at the Barretos Cancer Hospital (BCH), between August 2016 and July 2017. We performed three evaluations at different time points after chemoradiation treatment to compare changes in muscle function. Pelvic floor muscle function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…We also observed a high burden of urinary incontinence in patients with cervical cancer. Chemoradiation poses additional risks of weakening the pelvic floor muscle causing issues such as urinary incontinence 26 . Anticholinergics can be prescribed to treat bladder control issues which may improve the psychological wellbeing of survivors and overall quality of life; however, care must be taken to identify potential contraindications to anticholinergics.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed a high burden of urinary incontinence in patients with cervical cancer. Chemoradiation poses additional risks of weakening the pelvic floor muscle causing issues such as urinary incontinence 26 . Anticholinergics can be prescribed to treat bladder control issues which may improve the psychological wellbeing of survivors and overall quality of life; however, care must be taken to identify potential contraindications to anticholinergics.…”
Section: Discussionmentioning
confidence: 99%
“…Pelvic floor dysfunction is a common complication after cervical cancer surgery, with an incidence of up to 50% ( 2 , 5 ). The results herein demonstrated that age greater than 65 years, open surgery, total hysterectomy, and radiotherapy were risk factors of postoperative pelvic floor dysfunction in patients with cervical cancer (P<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…However, acute toxicity and diarrhea during radiation therapy for CC significantly increase the risk of severe late toxicity and affect the patient's QoL. Radiotherapy is known to cause fibrosis in bladder walls, which results in a low compliance of the bladder and explains the elevated risk of urinary urgency and frequency in patients who undergo primary radiotherapy [20,21]. Therefore, oncologists should consider a treatment strategy to minimize the development of PFD following adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%